Applicability of improved Dyson–McLean approach to creep deformation behaviour of tempered martensitic P9 steel. (4th July 2018) - Christopher, J.; Choudhary, B. K.
Abstract: Modelling creep deformation of tempered martensitic P9 steel in quenched and tempered, and simulated post weld heat treatment conditions has been performed in the framework of improved Dyson–McLean approach for wide range of stresses at 873 K. In this approach, kinetic creep law coupled with the set of first-order differential equations representing the evolution of microstructural internal-state-variables with strain/time has been employed to describe creep deformation behaviour of tempered martensitic steel. The optimised material constants associated with the model such as dislocation storage parameter ( K d ) and rate constants associated with the precipitate coarsening ( K p ) and solute depletion ( K s ) reflect the influence of two different heat treatments on creep characteristics examined in the present investigation. At all test conditions, good agreement between the predicted and experimental creep strain/strain rate-time data at 873 K has been observed. Further, good correlations have been obtained between the experimental and predicted steady-state creep rates and time to reach the specified strain levels for both the heat treatment conditions.